Enrichment and Characterization of Atrazine Degrading Bacterial Communities - Nikolina Udiković; Gordana Mendaš; Daša Filipčić; Dubravka Hršak (Food Technology and Biotechnology, 2003)
The objective of this study was to enrich and evaluate biotransformation activity of atrazine degrading bacterial communities originating from wastewater and soil of the herbicide factory, especially to assess their effectiveness for treatment of effluents from the production of atrazine. The enrichment of atrazine degrading bacteria was carried out in continuous-flow units under the inflow of mineral salts medium containing 25 mg/L of atrazine and 50 mg/L of yeast extract (AMS). After a 2-month cultivation at a dilution rate of 0.1 h–1, the enriched communities showed similar structure (determined by plating on selective agar plates) and similar degradation activity (complete disappearance of atrazine in AMS medium, monitored by HPLC analyses) as well as substantial mineralizing activity (50–60 % of atrazine released as carbon dioxide, determined by TIC analyses). The potential of the enriched communities for atrazine degradation in industrial wastewater was further studied in laboratory batch and continuous experiments with cells, immobilized or free in solution. Atrazine was completely degraded only in wastewater containing 25 % of mineral salts medium with cells free in the solution, while slower and incomplete degradation with accumulation of hydroxyatrazine was achieved with immobilized cells. Furthermore, there was no significant difference in the kinetics of atrazine degradation using different carrier materials for inoculum immobilization. Other s-triazine wastewater constituents, deethylatrazine (DEA) and deisopropylatrazine (DIA) were poorly degradable. Batch culture experiments in AMS medium amended with isopropylamine (IPA) and NaCl suggested that high salinity and high content of IPA in the industrial wastewater may be the major factors influencing the growth rate of atrazine degrading community and consequently the kinetics of atrazine degradation.